Application of Pont's index to a Pakistani population: a digital stereomicroscopic study - Shahid Fazal; Alam Mohammad Khursheed; Khamis Mohd Fadhli; Townsend Grant Clement (Sciendo, 2017)
To investigate the applicability of Pont's index for predicting maxillary and mandibular dental arch widths in a Pakistani population.